Penggunaan Kartu ATM Terhadap Konsumtivisme Mahasiswa Program Studi Pendidikan Ekonomi, Universitas Flores - Nande, Marsel; Muhammad, Ummy (Ekspektasi: Jurnal Pendidikan Ekonomi, 2024)
The aim of this research is to determine the effect of using ATM cards on the consumerist behavior of students in the Economic Education study program. The type of research used is explanatory which is used to identify why a phenomenon occurs and how variables influence each other, namely the use of ATM cards influences student consumptive behavior. The data collection technique uses documentation studies and questionnaires, the analysis tool uses simple regression analysis. The results show that the use of ATM cards has a significant effect on the consumerist behavior of economic education students with a percentage of 83%. The conclusion is that ATM cards do make it easier for students to carry out financial transactions, but on the other hand they can also encourage consumer behavior. The solution that can be given to reduce this is by providing education about financial literacy.